Better behavioral control in sharia investment decision: a literature review - Surendra Purusottama Rangga; Y Anni Aryani; Doddy Setiawan; Ibrahim Fatwa Wijaya; Setiyawan Gunardi (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - This study aims to identify factors that influence investment decisions. Furthermore, the researcher wants to show how sharia-compliant investment decisions act more rationally than conventional investment decisions. Method - This study employs the "charting the field" method by categorizing articles based on research themes and utilizing the VOSviewer application to analyze variable occurrences. The researchers used databases from Scopus.com and sinta.kemendikbud.go.id, covering publications from 2017 to 2024. Result - Investment decisions in the non-sharia sector are often influenced by excessive overconfidence and behavioral biases, which may lead to losses for investors. In contrast, sharia-compliant investment decisions tend to rely on more certain factors, emphasizing rationality based on financial literacy, behavioral control, and religiosity. Implication - This study highlights that investment decisions are primarily influenced by factors such as high confidence levels, uncertainty, herding bias, behavioral bias, and heuristic bias. Meanwhile, investors in the sharia sector tend to be more cautious and have better behavioral control, making the decision-making factors in sharia-compliant investments more applicable in practice. Originality - This study is relatively rare in both global and Indonesian contexts, providing insights into how sharia-compliant investments can serve as a viable option for investment decision-making.